The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.pone.0270740
|View full text |Cite
|
Sign up to set email alerts
|

Does knowing the influenza epidemic threshold has been reached influence the performance of influenza case definitions?

Abstract: Background Disease surveillance using adequate case definitions is very important. The objective of the study was to compare the performance of influenza case definitions and influenza symptoms in the first two epidemic weeks with respect to other epidemic weeks. Methods We analysed cases of acute respiratory infection detected by the network of sentinel primary care physicians of Catalonia for 10 seasons. We calculated the diagnostic odds ratio (DOR) and 95% confidence intervals (CI) for the first two epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…While ILI-ECDC was more commonly reported than ILI-WHO across all ages for the three infections, only ~ 15% of reported ILI-ECDC could be explained by test positivity for SARS-CoV-2, influenza A/B, or RSV. Prior studies have found higher rates of respiratory test positivity amongst those reporting ILI (and conversely, higher rates of ILI amongst influenza-positives), yet these estimates have generally been based on patients presenting to healthcare with symptoms of respiratory infection [ 8 , 9 , 12 14 , 17 , 18 , 41 ]. Such samples will be skewed towards more severe cases, as individuals with milder disease are less likely to seek healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While ILI-ECDC was more commonly reported than ILI-WHO across all ages for the three infections, only ~ 15% of reported ILI-ECDC could be explained by test positivity for SARS-CoV-2, influenza A/B, or RSV. Prior studies have found higher rates of respiratory test positivity amongst those reporting ILI (and conversely, higher rates of ILI amongst influenza-positives), yet these estimates have generally been based on patients presenting to healthcare with symptoms of respiratory infection [ 8 , 9 , 12 14 , 17 , 18 , 41 ]. Such samples will be skewed towards more severe cases, as individuals with milder disease are less likely to seek healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between ILI and influenza positivity remains complex, influenced by differing case definitions [ 10 , 11 ], changes in co-circulation of other viruses (notably respiratory syntactical virus (RSV) and SARS-CoV-2) across seasons [ 12 , 13 ], age-specific dynamics [ 14 ], and the non-specific nature of influenza symptoms [ 15 , 16 ]. Various studies have attempted to assess these relationships, but most have limited their scope to clinical settings, and/or focussed solely on influenza, and/or restricted to patients already reporting ILI or Acute Respiratory Illness (ARI) [ 7 9 , 12 14 , 17 , 18 ]. Similarly, influenza vaccine effectiveness evaluation typically uses disease endpoints, rather than protection from infection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Various studies have attempted to assess these relationships, but most have limited their scope to clinical settings, and/or focussed solely on influenza, and/or restricted to patients already reporting ILI or Acute Respiratory Illness (ARI). [7][8][9][12][13][14]17,18 Similarly, influenza vaccine effectiveness evaluation typically uses disease endpoints, rather than protection from infection. 19 Here we use the Office of National Statistics COVID-19 Infection Survey (CIS) to investigate the relationship between respiratory infection test positivity and ILI/other self-reported symptoms.…”
Section: Introductionmentioning
confidence: 99%